Development of mass-customization engine for house finishing / Norkhairiah Abu Bakar - Abu Bakar, Norkhairiah (2004)
Nowadays, people try to grip with new technology of computer especially in expert system revolution. The consistent knowledge as well as the effectiveness of giving solutions increases the demand of developing expert systems in many areas. For examples, the successful of construction term in the real life may lead to the involvement of expert system mechanism. The first purpose of developing the Mass- Customization Engine for House's Finishing is to satisfy user requirement especially in customizing the house's finishing. Secondly is to construct model of information flow in customizing house base on current model of information flow of mass customization. The knowledge in this system is represented using rules; while the forward inference technique and backtracking technique is used for the reasoning process which is the backtracking technique can customize user's option. The system also provides the explanation facilities that include explaining facility that give the explanation on certain term on the interfaces. Although the system is successfiilly implemented, there are still weaknesses and the future enhancing are support.